Analisis Strategi Peningkatan Mutu Guru Sekolah Dasar Negeri Sugiwaras Kecamatan Babat Toman Kabupaten Musi Banyuasin - Nursiha, Siti; Nawawi, Effendi; Hestirinaih, Deby Chintia (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
The quality of education is greatly influenced by the professionalism and competence of teachers. Therefore, this study aims to determine the quality of teachers and strategies to improve the quality of teachers at SD Negeri Sugiwaras. This research used a qualitative approach and descriptive qualitative method. The strategies used by SD Negeri Sugiwaras to improve the quality of teachers are good, but special attention is needed in mastering technology and work culture within the school environment. In addition, the socialization of the organization's vision, mission, and objectives to all teachers and staff at SD Negeri Sugiwaras needs to continue to be carried out through meetings, discussions, and informal meetings. Furthermore, SD Negeri Sugiwaras can also carry out mentoring or coaching programs for teachers who need special guidance in developing their teaching quality and professionalism. This mentoring program can be conducted by senior teachers or the principal who already have experience and expertise in the field. With this mentoring program, it is hoped that teachers who need special guidance will be assisted in developing themselves and improving the quality of their teaching. Moreover, SD Negeri Sugiwaras can also conduct regular evaluations of teacher performance. This evaluation can be carried out by the principal or the curriculum development team that has been formed. With regular evaluation of teacher performance, it is expected to provide positive and negative feedback to improve teacher performance and the quality of teaching provided. This evaluation can also help teachers identify their weaknesses and strengths in teaching.